Effect of plant age and water stress on the incidence of post flowering stalk rot of maize caused by Fusarium verticillioides - and RENU GUPTA, M.K. KHOKHAR*, S.S. SHARMA (Indian Phytopathology, 2014)
Eight different stages of maize plants of 25, 35, 45, 55, 65, 75, 85 and 95 days were evaluated for the effect of host age on PFSR under artificial inoculations. The intensity of disease varied from 2.6 to 7.7 at these eight different stages. Plant is most susceptible when it is 55 days old with disease rating i.e. 7.7, followed by 65 days and 25 days old plants was least susceptible with 2.6 disease rating. So, it could be concluded that 55 to 65 days old plants were highly susceptible to F. verticillioides which coincides with silking stage. Stalk rot incidence was significantly reduced 60.37 to 15.03 per cent by when additional irrigation provided to the crop at tasselling and silking stage. Maximum lodging 47.68% was noticed at irrigation level- I (6-7) while, minimum at level- II with 11.14%. All the three irrigation levels differed significantly with each other and least disease rating 3.2 observed at irrigation level- II, followed by 5.2 at level- I. whereas, maximum disease rating 7.3 was recorded with irrigation level III. Low inoculum density of pathogen i.e. 7.1 c.f.u. of F. verticillioides X 104/g soil at irrigation level II whereas, irrigation level-III showed with 15.9 c.f.u. of F. verticillioides X 104/g soil which was significantly superior with irrigation level-I i.e. 11.4. c.f.u. of F. verticillioides X 104/g soil. The effect of different irrigation levels on grain yield recorded in irrigation level-I yielded 1123.61 g/10 plants, whereas, and irrigation level- II and irrigation level- III recorded 1450.22 and 939.39 g/10 plants, respectively.